2013
DOI: 10.2458/azu_js_rc.55.16303
|View full text |Cite
|
Sign up to set email alerts
|

Extraneous Carbon Assessments in Radiocarbon Measurements of Black Carbon in Environmental Matrices

Abstract: ABSTRACT. Extraneous carbon (C ex ) added during chemical processing and isolation of black carbon (BC) in environmental matrices was quantified to assess its impact on compound specific radiocarbon analysis (CSRA). Extraneous carbon is added during the multiple steps of BC extraction, such as incomplete removal of solvents, and carbon bleed from the gas chromatographic and cation columns. We use 2 methods to evaluate the size and  14 C values of C ex in BC in ocean sediments that require additional pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…The chemical extraction procedure (prior to PCGC) was not evaluated (apart from processing a blank for GC/MS analysis, see Results and Discussion) since it is a relatively simple procedure that does not require derivatization and thus it is unlikely to introduce as much C ex compared to PCGC isolation and solvent removal. It should be noted that evaluating the chemical extraction becomes relevant if there are co-eluting compounds in the reagents and solvents used in the extraction procedure and/or extensive chemical pre-treatments are used (Ziolkowski and Druffel 2009;Coppola et al 2013). Our results showed that our extraction methods do not contribute co-eluting compounds (see Results and Discussion).…”
Section: Correction For the Amount And 14 C Content Of C Exsupporting
confidence: 57%
See 4 more Smart Citations
“…The chemical extraction procedure (prior to PCGC) was not evaluated (apart from processing a blank for GC/MS analysis, see Results and Discussion) since it is a relatively simple procedure that does not require derivatization and thus it is unlikely to introduce as much C ex compared to PCGC isolation and solvent removal. It should be noted that evaluating the chemical extraction becomes relevant if there are co-eluting compounds in the reagents and solvents used in the extraction procedure and/or extensive chemical pre-treatments are used (Ziolkowski and Druffel 2009;Coppola et al 2013). Our results showed that our extraction methods do not contribute co-eluting compounds (see Results and Discussion).…”
Section: Correction For the Amount And 14 C Content Of C Exsupporting
confidence: 57%
“…We can also use the uncorrected F 14 C values of C 29 and C 31 n-alkanes isolated from the grass to estimate C ex derived from the entire sample procedure (chemical extraction + PCGC + solvent removal), assuming that the grass nalkanes have the same 14 C content of the bulk grass (our initial assumption) and thus any deviation represents C ex ( 14 C-free) added during the entire sample procedure (assuming addition of modern C ex during PCGC isolation is relatively insignificant; Druffel et al 2010;Kramer et al 2010;Coppola et al 2013). Our estimates show that ~ 0.91 ± 0.46 to 1.3 ± 0.65 µg C per minute, per 50 (1µl) injections is derived from the entire sample preparation procedure versus 0.75 ± 0.38 derived from PCGC isolation and solvent removal only (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations